2016
DOI: 10.4103/1477-3163.182809
|View full text |Cite
|
Sign up to set email alerts
|

The well-accepted notion that gene amplification contributes to increased expression still remains, after all these years, a reasonable but unproven assumption

Abstract: “Gene amplification causes overexpression” is a longstanding and well-accepted concept in cancer genetics. However, raking the whole literature, we find only statistical analyses showing a positive correlation between gene copy number and expression level, but do not find convincing experimental corroboration for this notion, for most of the amplified oncogenes in cancers. Since an association does not need to be an actual causal relation, in our opinion, this widespread notion still remains a reasonable but u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…On the other hand, the analysis of SCNAs in FOXD2-AS1 and LINC00968 show that FOXD2-AS1 is not signi cantly focally ampli ed or deleted, but LINC00968 is signi cantly focally ampli ed in invasive breast carcinoma. Ampli cation is a genetic mechanism of overexpression that is a well-accepted concept in cancer genetics (44). Ampli cation of FOXD2-AS1 might be played a role in the breast cancer tumorigenesis, but it is thought that ampli cation might not relate to the low expression of LINC00968 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the analysis of SCNAs in FOXD2-AS1 and LINC00968 show that FOXD2-AS1 is not signi cantly focally ampli ed or deleted, but LINC00968 is signi cantly focally ampli ed in invasive breast carcinoma. Ampli cation is a genetic mechanism of overexpression that is a well-accepted concept in cancer genetics (44). Ampli cation of FOXD2-AS1 might be played a role in the breast cancer tumorigenesis, but it is thought that ampli cation might not relate to the low expression of LINC00968 in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have not shown whether tumors carrying amplified RRM2B have increased RRM2B expression, which might directly impact its role in cancer. Multiple studies have observed that gene amplifications do not always lead to increased expression [31]. Thus, to confirm increased expression, we used mRNA expression data from three TCGA studies (OV, BRCA, HNSC), and found that tumors with gains and amplifications had significantly increased RRM2B mRNA expression in all three cancer types studied (Supplementary…”
Section: Tumors With Rrm2b Amplifications Exhibit Increased Rrm2b Expmentioning
confidence: 99%
“…The involvement of highly conserved and ubiquitous transmembrane tyrosine kinase receptors, namely fibroblast growth factor receptors (FGFRs), in tumorigenesis, cell fate determination, survival, motility, angiogenesis, and malignantization of tumor cells, as well as in reduced sensitivity to anticancer therapeutics and poor prognosis is extensively documented [5]. Notably, genetic alterations in FGFR1, such as amplification or an increase in gene copy number, are positively correlated with overexpression and are more prevalent than genetic aberrations in FGFR2, FGFR3, and FGFR4 [5,6]. Hence, Lehnen et al, studying the role of the FGFR1 gene copy number and expression pattern in patients with PDAC, suggested that the association between FGFR1 amplification, mRNA or protein expression, and the proliferative potential of PDAC cells can be exploited for therapeutic purposes using FGFR1 inhibitors [7].…”
Section: Introductionmentioning
confidence: 99%